Ocean acidification effects on the stress response in a calcifying antarctic coastal organism: The case of Nacella concinna ecotypes. (May 2021) - de Aranzamendi, M.C.; Servetto, N.; Movilla, J.; Bettencourt, R.; Sahade, R.
Abstract: Ocean acidification (OA) could become a serious threat for the Antarctic marine ecosystem over coming years, as the solubility of atmospheric CO2 and CaCO3 minerals increases at lower temperatures. We evaluated the effect of OA on the stress response of the limpet Nacella concinna by measuring gene expression levels. The experiment was performed with the two ecotypes (Littoral and Sublittoral) of the species during 54 days (IPCC, 2019 scenario RCP8.5; control, 375 ppm; low-pH treatment, 923 ppm). Exposure to low-pH treatment during 15 days triggered the down-regulation of two heat-shock protein genes (HSP70A, HSP70B) only in sublittoral individuals. Little variation in the relative expression values of all genes in both ecotypes was observed probably, due to a historical exposure to the substantial daily natural pH fluctuations recorded in the study area during the experiment. This study provides relevant baseline data for future OA experiments on coastal species in Antarctica. Graphical abstract: Unlabelled Image Highlights: An ocean acidification experiment with the two ecotypes of Nacella concinna No noticeable low-pH effects on the stress response in the Antarctic limpet Adaptation of both ecotypes to natural pH fluctuations in the fjord might be occurring.